NONVERBAL COMMUNICATION PERFORMED BY FOREIGN ENGLISH TEACHER - Jihan Ananda; Dadang Solihat; Yayan Suryana (University of Kuningan, 2020)
This paper specifically aims at knowing the types of nonverbal communications performed by the foreign English teacher based on Schmitz’s (2012) theory and finding out the students’ responses toward the foreign English teacher’s nonverbal communication. Qualitative research design was applied in this research. The participants of this research were the foreign English teacher and the students of class VII A MTsN 2 Kuningan. The data were collected through observation, interview, and questionnaire. The data were analyzed both qualitative and quantitative. The results of the research revealed that the foreign English teacher performed 3 types of nonverbal communication: 1) kinesics (includes gesture: emblems and illustrators, head movements and posture, eye contact, and facial expression); 2) vocalics; and 3) proxemics. However, the foreign English teacher did not perform adaptors and haptics in the classroom. He confessed that he did not really do certain gestures while feeling nervous, and for the American teacher, haptics (communication by touch) is a sensitive thing, and a difficult area. Regarding the students’ responses, they felt motivated learning English with the foreign English teacher because it made them happy, excited, proud, enthusiastic, and have willingness to learn more. It was showed that 89,6% of the students responded positively toward nonverbal communication performed by the foreign English teacher in teaching learning process, and being responded negatively by 10,4%. Furthermore, it emphasizes that teachers should be aware in applying nonverbal communication to create educative interesting atmosphere for the students and make the teaching learning process effective as well as motivating them.Keywords: nonverbal communication; foreign teacher; student’s response.